Supplementation of eicosapentaenoic acid-rich fish oil attenuates muscle stiffness after eccentric contractions of human elbow flexors - Yosuke Tsuchiya; Kenichi Yanagimoto; Hisashi Ueda; Eisuke Ochi (Taylor & Francis Group, 2019)
Background This study aimed to investigate the effect of supplementation of fish oil rich in eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) on the damage of the biceps brachii after eccentric contractions (ECCs) of the elbow flexors, particularly focusing on muscle stiffness. Methods Sixteen men were included in this double-blind, placebo-controlled, parallel design study and the participants were randomly assigned to the EPA and DHA supplement group (EPA, n = 8) and placebo group (PL, n = 8). They consumed either EPA 600 mg and DHA 260 mg per day or placebo supplement for 8 weeks prior to exercise. Moreover, they performed six sets of 10 ECCs at 100% maximal voluntary contraction (MVC) using a dumbbell. Changes in MVC torque, range of motion (ROM), upper arm circumference, muscle soreness, muscle echo intensity, and muscle stiffness were assessed before exercise; immediately after exercise; and 1, 2, and 5 days after exercise. Results MVC torque and ROM were significantly higher in the EPA group than in the PL group after ECCs (p < 0.05). Muscle soreness, upper arm circumference, and muscle echo intensity were significantly higher in the PL group than in the EPA group after ECCs (p < 0.05). In addition, muscle stiffness at 150° was significantly higher in the PL group than in the EPA group immediately after ECCs (p < 0.05). Conclusion The present study showed that EPA and DHA supplementation has a positive role in inhibiting muscle stiffness after ECCs. Trial registration This trial (UMIN000028165) was registered on 10th/July/2017.